SCIENTIFIC INTEREST AND LEVEL OF CREATIVITY AMONG HIGHER SECONDARY STUDENTS IN KANYAKUMARI DISTRICT - M.R., Ayishajuhi; Sreeletha, R. (International Journal of Research -GRANTHAALAYAH, 2020)
The present study investigated on scientific interest and level of creativity among higher secondary students in Kanyakumari district. The objective of the study was to find out the level of scientific interest and level of creativity among higher secondary students. The study also investigated to find out the significant difference in scientific interest and level of creativity among higher secondary students with respect to the gender, locality of institution, medium of instruction, type of family, type of school and religion. The investigator used normative survey method for investigation. Data was collected from a sample of 300 higher secondary students. The investigator used Scientific Interest Inventory (Ayishajuhi and Sreeletha, 2018) and Creativity test (Devishree and Sam Sandra Raj, 2009). The statistical techniques used were percentage analysis, t-test, ANOVA and Person Product moment (r). The findings revealed that the level of scientific interest and level of creativity among higher secondary students at moderate level. There was no significant difference in scientific interest and level of creativity among higher secondary students with respect to locality of school, medium of instruction, type of school and religion, but significant difference existed in the scientific interest and level of creativity among higher secondary students with respect to gender and type of family.